Pravice (in dolžnosti) manjšin v večkulturnih družbah - Devetak, Silvo (Razprave in gradivo - Inštitut za narodnostna vprašanja (1987), 1987)
Fourty years since the passing of the Universal Declaration on Human Rights it can be asserted that the ethnic or national minority problematics remains unsolved. Furthermore, new social and political dilemmas occured. Many states attempt to "solve" the problem with assimilationist policy or are pretending that minority problem does not exist at all. Data clearly show that there are but few modern political entities that can pass as ethnically homogeneus; therefore the minority problematics is one of universal character. The typology of the acute minority problems in the modern world is all but uniform. New problems are constantly arising to join those well-known ethnic problems in Europe. Numbers of domestic as well as international difficulties are caused by unsolved interethnic problems within recently established states, notably in Africa. We are facing the acute problems of the so-called indigenous population in the America, Australia and the European North. Questions arise, how to treat tenfolds of million people who were forced to abandon their homes for employment, political and religious presuasions, because of wars, poverty or viloence? The proces of integration they are forced to undergo in their new environments gives rise to series of new and complex social, economical and political problems. Surely that of cultural and ethnical desintegration is outmost painful. The atrained relation between "inherent" culture and that of the "domicile" is bound to resolve of the later. According to the author's opinion, these complex problems cannot be dealt with by mere sets of legal, economic and the like measures. Rather, complex and profound changes should be sought for on political, cultural and economic level in multicultural and or multinational societies, by means of appropriatedomestic policoes. Minorities should be granted full participation in administering the regions they occupy. No progress in this respects can occur without a general recognition of the need for tolerance and coexistance.This must be, stress the author, first sought for in our own environment, in order to attain proper moral standing for extending minority-rights struggle into international arena.